Indigenous tourism in Asia and Malaysia: the bibliometric analysis - Syakir Amir Ab Rahman,; Fatin Nabila Che Zuki,; Alias Abdullah,; Illyani Ibrahim,; M. Zainora Asmawi,; Rajabi Abdul Razak Nor Nadiah Najib,; Maimunah Abdul Aziz, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Indigenous tourism has gained popularity among tourists seeking diverse cultural experiences. This study provides a comprehensive bibliometric analysis of Indigenous tourism research in Asia, especially in Malaysia, covering publications from 1993 to 2024. Using the Scopus database, 143 documents were analysed with VOSViewer, Microsoft Excel, and Harzing’s Publish or Perish to map co-authorship networks, assess citation metrics, and track thematic trends. The findings indicate a significant rise in research output after 2000, peaking in 2016 (14 articles) and 2017 (13 articles), with 2010 and 2016 registering the highest average number of citations. Most publications were journal articles (102) written in English (138), with Australia leading in research output (47 documents), followed by the United Kingdom (18), Canada (15), and Malaysia (7). Keyword analysis revealed a strong emphasis on ‘Indigenous Tourism’ (74 occurrences), followed by ‘Indigenous Population’ (35), ‘Tourism Development’ (29), and ‘Ecotourism’ (21), which highlights sustainability, heritage, and empowerment as central research themes. The most active institution was the University of Queensland (17 publications), and prominent authors included L. Ruhanen (13 articles) and M. Whitford (9 articles). The field recorded 2,193 total citations, an h-index of 27, and a g-index of 39, which signals robust scholarly engagement. The study also observed increased collaboration among researchers, institutions, and countries, with a growing trend in interdisciplinary studies. It is recommended that future research promote multilingual dissemination, increase the participation of Indigenous communities, and expand beyond the dominant Western focus to include underrepresented regions such as Southeast Asia. These steps are vital for creating more inclusive, equitable, and culturally respectful Indigenous tourism frameworks that align with the goals of sustainable development and the preservation of heritage.